2016
DOI: 10.1128/aem.04052-15
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Toxicities of Salts on Microbial Processes in Soil

Abstract: Soil salinization is a growing threat to global agriculture and carbon sequestration, but to date it remains unclear how microbial processes will respond. We studied the acute response to salt exposure of a range of anabolic and catabolic microbial processes, including bacterial (leucine incorporation) and fungal (acetate incorporation into ergosterol) growth rates, respiration, and gross N mineralization and nitrification rates. To distinguish effects of specific ions from those of overall ionic strength, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(88 citation statements)
references
References 54 publications
5
71
0
1
Order By: Relevance
“…Controls involved dilute ethanol replacing melatonin (see below) and/or sterile Milli-Q water replacing cadmium. These concentrations were selected to be within the range of those reported to induce effects on soil microbial activities in previous studies for cadmium (Cáliz et al, 2013, Wood et al, 2016) and salt (Rath et al, 2016). Based upon preliminary studies, soils were treated to 80-90% field capacity, to ensure all soils were sufficiently exposed to stressor and melatonin.…”
Section: Methodsmentioning
confidence: 99%
“…Controls involved dilute ethanol replacing melatonin (see below) and/or sterile Milli-Q water replacing cadmium. These concentrations were selected to be within the range of those reported to induce effects on soil microbial activities in previous studies for cadmium (Cáliz et al, 2013, Wood et al, 2016) and salt (Rath et al, 2016). Based upon preliminary studies, soils were treated to 80-90% field capacity, to ensure all soils were sufficiently exposed to stressor and melatonin.…”
Section: Methodsmentioning
confidence: 99%
“…The extremely low contribution of ergosterol to MBC (Djajakirana et al, 1996;Joergensen and Wichern, 2008) indicates that the concentration of saprotrophic fungi is probably very low in the current paddy soils. Other studies also showed fungal growth rates are less sensitive to salinity than bacterial growth rates after application of fresh substrate (Rath et al, 2016(Rath et al, , 2019Dang et al, 2019). This might be different for the contribution of fungal residues to SOC under saline conditions (Khan et al, 2016) as the biomass of many soil fungi declines when exposed to salinity (Sardinha et al, 2003).…”
Section: Distinct Microbial Response Of Different Soils Indicate Soilmentioning
confidence: 99%
“…Soil salinity not only affects microbial community composition and abundance but also affects microbial functions, i.e. enzymatic and metabolic processes (Morrissey et al 2014;Rath et al 2016). High salinity can reduce microbial enzyme activity (Singh 2016).…”
Section: Culturable Diversity Of Endophytic Fungi In S Europaeamentioning
confidence: 99%